Comparative Finite Element Analysis of Al 7075-T6 and Al 2024-T4 for the Upright Component of a Racing Car - Rizkyansyah Alif Hidayatullah; Samuel Adi Nugroho; Rizaldy Hakim Ash Shiddieqy (G-Tech: Jurnal Teknologi Terapan, 2025)
Topology optimization is a method for reducing mass without compromising structural strength, resulting in an optimal design tailored to the loads acting on the Upright. This study aims to evaluate the stress and deformation of the front Upright design of racing car before optimization and analyze the stress, deformation, and safety factor after topology optimization. Various mass retain percentages are considered to identify the best design that can be manufactured using a 3-axis CNC milling machine.  The research includes load analysis on the front Upright during deceleration, acceleration, and cornering, which subjects the Upright bearing.  The front Upright design is simulated using static structural analysis finite element with ANSYS software . Topology optimization simulations are then conducted with mass retain percentages of 60% dan 40%. Static structural simulations are performed for each optimized design.  The results indicate that the Upright design with a 40% mass retain using At a mass retain of 40% of the Al 2024 T4 material, the mass reaches 459 g with a total deformation of 0.0416 mm and a maximum stress of 84,997 Mpa. 0.04161. The research results obtained lighter materials so that 3-axis CNC production with three stages or sides using one jig and suggested that it is very necessary to validate the simulation results and ensure the design meets technical and safety specifications.